2021
DOI: 10.1021/acsmedchemlett.1c00456
|View full text |Cite
|
Sign up to set email alerts
|

Small Peptides for Inhibiting Serum Amyloid A Aggregation

Abstract: Deposition of human serum amyloid A (SAA) amyloids in blood vessels, causing inflammation, thrombosis, and eventually organ damage, is commonly seen as a consequence of certain cancers and inflammatory diseases and may also be a risk after SARS-COV-2 infections. Several attempts have been made to develop peptide-based drugs that inhibit or at least slow down SAA amyloidosis. We use extensive all-atom molecular dynamic simulations to compare three of these drug candidates for their ability to destabilize SAA fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…One of the most difficult and puzzling problems in the context of neurological disorders is associated with the abnormal metabolic activity of proteins, peptides, and essential amino acids. It is well established that certain peptides, as well as proteins, form aggregated structures. For example, Hansmann and co-workers reported the formation of fibrillar etiologies by serum amyloid A, α-synuclein, Aβ-peptide, amylin, and other small protein complexes . Other than such protein and peptides, single amino acids bearing the aromatic moieties in their structures are also reported to form toxic fibrillar etiologies. , For example, the abnormal metabolic activity of phenylalanine (Phe) results in the accumulation of unprocessed Phe in the body, leading to the formation of toxic fibrillar etiologies in various parts of the body. , The same is reported in the case of the abnormal disorder tyrosinemia type II, which is associated with the formation of fibrillar etiologies of tyrosine.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most difficult and puzzling problems in the context of neurological disorders is associated with the abnormal metabolic activity of proteins, peptides, and essential amino acids. It is well established that certain peptides, as well as proteins, form aggregated structures. For example, Hansmann and co-workers reported the formation of fibrillar etiologies by serum amyloid A, α-synuclein, Aβ-peptide, amylin, and other small protein complexes . Other than such protein and peptides, single amino acids bearing the aromatic moieties in their structures are also reported to form toxic fibrillar etiologies. , For example, the abnormal metabolic activity of phenylalanine (Phe) results in the accumulation of unprocessed Phe in the body, leading to the formation of toxic fibrillar etiologies in various parts of the body. , The same is reported in the case of the abnormal disorder tyrosinemia type II, which is associated with the formation of fibrillar etiologies of tyrosine.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is in line with the requirement for DAF-16, which was shown to promote protective hyper-aggregation (Cohen et al, 2006) that sequesters highly toxic oligomers to create large fibrils of lower toxicity (Shankar et al, 2008). However, similarly to other short peptides that were predicted by simulations to reduce aggregation (Jana et al, 2021), the 5MER peptide was found to inhibit the aggregation of serum amyloid A in in-vitro experiments (Hemed-Shaked et al, 2021). This apparent contradiction may result from different properties of the 5MER peptide in the absence of ancillary biological molecules in in-vitro assays that may shape its effect on protein aggregation.…”
Section: Discussionmentioning
confidence: 83%
“…Even full-length d -Aβ40 and d -Aβ42 proteins where the sequence of amino acids is also reversed, named retro inverso proteins, compared to the wild-type L variant have been studied computationally and found to be stable in short fibrillar fragments, which could lead to faster aggregation into fibrils while bypassing the toxic oligomers as reported by Xi and Hansmann . This methodology has also been shown to be promising for inhibiting the aggregation of the amylin protein or the human serum amyloid A into fibrils. The increased number of studies using d -peptides as possible inhibitors of amyloid aggregation emphasizes their high potential for treating amyloid-based diseases.…”
Section: Resultsmentioning
confidence: 95%